Management of Endometrial Hyperplasia With a Levonorgestrel-Releasing Intrauterine System: A Korean Gynecologic-Oncology Group Study. Issue 4 (May 2016) - Kim, Mi Kyoung; Seong, Seok Ju; Kim, Jae-Weon; Jeon, Seob; Choi, Ho Sun; Lee, In-Ho; Lee, Jong Hak; Ju, Woong; Song, Eun Seop; Park, Hyun; Ryu, Hee-Sug; Lee, Chulmin; et al.
Abstract : Objective: The aim of the study was to evaluate the efficacy of the levonorgestrel intrauterine system (LNG-IUS) for treatment of endometrial hyperplasia (EH). Methods: A prospective multicenter study was conducted from November 2010 to March 2014. Patients with histologically confirmed EH were treated with LNG-IUS. At 3, 6, and 9 months after LNG-IUS insertion, follow-up endometrial aspiration biopsies with the LNG-IUS in the uterus were undertaken. At the 12th month of follow-up, endometrial tissues were obtained via 2 methods: endometrial aspiration biopsy with the LNG-IUS in the uterus, followed by dilatation and curettage (D&C) after LNG-IUS removal. The primary outcome was the regression rate at 12 months after LNG-IUS insertion, and the secondary outcome was the consistency of the results between the endometrial aspiration biopsy and the D&C. Results: The study population comprised 75 patients, including 37 with simple hyperplasia without atypia; 3 with atypical simple hyperplasia; 23 with complex hyperplasia without atypia, and 12 with atypical complex hyperplasia. Of these patients treated with the LNG-IUS, 38 (50.7%) were followed up at 12 months after LNG-IUS insertion. The complete regression rate at 12 months was 94.7% (36/38): 100% (6/6) of patients with atypical EH and 93.7% (30/32) with EH without atypia. In all of the cases (100%, 36/36), patients achieved complete regression within 3 months of LNG-IUS insertion. A comparison of the pathologic results from endometrial aspiration biopsy and D&C was carried out for 15 patients. In the histologic results by endometrial aspiration biopsy, 14 patients were diagnosed as "normal endometrium" and 1 as "insufficient tissue for pathologic evaluation." Among the 14 cases of normal endometrium by endometrial aspiration biopsy, 1 was diagnosed as "residual EH" by D&C, and the 1 case with insufficient tissue was diagnosed as normal endometrium by D&C. Conclusions: Levonorgestrel intrauterine system is an effective and favorable method for treatment of EH.